On the system of temps of Uzbek classical music - Rasulov Marufjon Mamirjon ogli (Research Parks Publishers, 2021)
In this article we can see the temps that have become the basis of our Uzbek classical music. In the coverage of the subject of this temp, we can see that the issues of